Influence of organizational culture on organizational performance, perceived obstacles and technology usage intention amongst small and medium enterprises in Malaysia - Shahron, Syairah Aimi (2011)
The failure to adopt and absorb the benefits of advanced technologies (AMT) for their own advantage can hinder small and medium companies from becoming or remaining competitive in the global market. Therefore, this study aims to investigate the relationship between organizational culture on the perceived obstacles of AMT adoption, organizational performance and technology usage intention. In addition this study seeks to determine the role of perceived benefits of AMT adoption as mediator on the relationship between organizational performance and technology usage intention. Based on the gaps in the body of knowledge and objectives of the study theoretical framework were developed. Based on the data collected from 152 SME manufacturers only 140 SME manufacturers were qualified for further analysis. The data was analyzed using Statistical Package for Social Science (SPSS) version 15.0 (Pearson Correlation, Multiple Regression and Hierarchical Mediated Regression). Competing Value Framework which consists of four culture: group, developmental, rationale and hierarchy culture proposed by Quinn and Rohrbaugh (1981) was used in this study. Results indicate that regardless of the organizational culture, firms perceived that financial, knowledge, and infrastructure and external support are the obstacles towards the technology adoption. However, it was found, the higher the group or the rationale culture, the less likely firms perceived people resistance as obstacles towards technology adoption. Based on this study, it was also found that high rationale culture value in the organization will lead to the high level of technology usage intention. In terms of perceived benefits, firms that perceived high operational and managerial benefits as a result of adopting the technology have higher technology usage intentions. Meanwhile, for perceived obstacles, the result showed that the higher firms perceived people resistance and knowledge as an obstacle toward technology adoption, the lower their technology usage intention, while, the higher firms perceive financial, and infrastructure and external support obstacles, the higher their technology usage intention. This study suggests that organization with stronger elements of group culture and rationale culture are more likely to experience higher performance. This study also found that performance level impact the way firms perceived benefits of AMT adoption. This implies that, the higher the performance of the organizations, the more likely they perceived the operational, managerial and competitive benefits as a result from AMT adoption. Further analysis on this study signifies that the effect of organizational performance towards technology usage intention is greater when these firms perceived higher operational and managerial benefits as a result of the technology adoption. This study offered several implications for both the academic and practitioner audience. This study has covered the identified gaps and added value to the knowledge on the field of advanced technology adoption and organizational culture. Meanwhile, practical implications addressed the contributions made towards improving the advanced manufacturing adoption amongst SME.